Kinematic characterization of residual deformities in idiopathic clubfoot initially treated with the Ponseti method: gait analysis using the Heidelberg Foot Model - Chen, Qiuyue; Salami, Firooz; Putz, Cornelia; Wolf, Sebastian Immanuel (Journal of children's orthopaedics, 2025)
Purpose: This study aimed to investigate foot kinematics during gait in individuals with idiopathic clubfoot initially treated with the Ponseti method, focusing on clubfoot-specific deformities, to improve the understanding of posttreatment functional impairments. Methods: In this prospective cohort study, 23 patients with treated idiopathic clubfoot (34 feet) were compared with 15 age-matched healthy controls (30 feet). Gait analysis was performed using the Heidelberg Foot Model. To characterize residual clubfoot deformities, selected kinematic parameters included medial arch and subtalar angles, as well as intersegmental angles between hindfoot-shank and forefoot-hindfoot, based on more functional joint centers. Within the patient group, potential influence of additional surgical interventions was explored. Results: Compared with controls, treated idiopathic clubfoot exhibited significant reductions in hindfoot sagittal and transverse range of motion, forefoot sagittal range of motion, and medial arch mobility. Equinus deformity was not present posttreatment, as dorsiflexion metrics during stance did not differ significantly. However, plantarflexion range of motion during the transition to swing was reduced. In addition, treated idiopathic clubfoot showed persistent subtalar inversion and hindfoot varus, increased mid-stance adductus in both hindfoot and forefoot, and pronounced arch stiffness during transition to swing. Within the patient group, ankle and subtalar capsulotomy was associated with increased medial arch cavus. Conclusion: Patients with treated idiopathic clubfoot exhibit a functionally stiffer foot with altered alignment during gait, contributing to impaired limb advancement. The results expand the understanding of residual clubfoot deformities and highlight the importance of detailed functional assessment posttreatment, providing a foundation for future research. Level of evidence: Level II, prognostic study.
First published online September 2, 2025
Gesehen am 08.01.2026